Efficacy of initial combination with belimumab in newly diagnosed childhood-onset lupus nephritis: a single-centre historical control study - Yu Shi; Jing Chen; Hong Xu; Qian Shen; Yinv Gong; Li Sun; Qijiao Wei; Yifan Li; Xiaomei Zhang; Shuhua Liu; Haimei Liu; Wanzhen Guan; et al. (Lupus Science and Medicine)
Objective To explore the efficacy of initial treatment of newly diagnosed childhood-onset lupus nephritis (cLN) with combination of belimumab and either cyclophosphamide, mycophenolate mofetil, tacrolimus or multitargeted therapy.Methods A historical control study was conducted on children aged 5–17 years with newly diagnosed cLN. All patients recruited met the 2012 Systemic Lupus International Collaborating Clinics and/or 2019 European League Against Rheumatism/American College of Rheumatology classification criteria for SLE, and the 2003 International Society of Nephrology/Renal Pathology Society histopathological criteria for LN. The primary endpoint was primary efficacy renal response (PERR) at 12 months, and secondary endpoints included complete renal response (CRR), lupus low disease activity state (LLDAS) and remission (Definitions of Remission in Systemic Lupus Erythematosus (DORIS)) at 12 months, changes of SLE Disease Activity Index (SLEDAI) and dose of glucocorticoid (GC).Results A total of 101 patients were included with 38 patients in the belimumab group and 63 patients in the standard immunotherapy group. There were no statistically significant differences between the two groups at baseline. At 12 months, compared with the standard immunotherapy group, more patients in the belimumab group had a higher PERR (97.1% vs 80.0%, χ2=3.965, p=0.046), CRR (94.1% vs 76.6%, χ2=4.679, p=0.031), LLDAS (75.0% vs 18.6%, χ2=27.84, p<0.001) and DORIS (34.4% vs 11.9%, χ2=6.626, p=0.01). The belimumab group had faster and greater reductions in SLEDAI and dose of GC (p<0.05), with a significantly higher proportion of patients with dose of GC ≤7.5 mg/day (82.9% vs 30.4%, χ2=19.737, p<0.001). In the standard immunotherapy group, 4 patients (6.3%) experienced a decline in estimated glomerular filtration rate of 30% or more at 12 months, while no patients in the belimumab group experienced worsening of renal function. There were no serious adverse events reported in two groups, and there was no significant difference in the occurrence of infection between the two groups.Conclusion This study reported for the first time the effectiveness of combined belimumab therapy in a Chinese cohort of patients with cLN. The strategy of initial combination with belimumab helps achieve treatment targets earlier and faster GC tapering. And initial combination therapy in children with cLN with high disease activity may yield more significant benefits.